Motivational factors in learning chemistry among chinese national-type secondary school students in Negeri Sembilan - Nordin, Aziz; Jenne Lee, Ling Huey (2010)
The purpose of this study is to investigate the internal and external motivational factors in learning Chemistry among Chinese National-Type Secondary School students in Negeri Sembilan. This study is also aimed to find out the relationship among motivational factors and academic performances in Chemistry. This study also aimed to find out the dominant motivational factor in learning Chemistry among the factors studied. A total of 203 Form Four students from all three Chinese National-Type Secondary Schools in Negeri Sembilan were chosen to participate in this study by using random sampling method. The motivational factors in learning Chemistry were measured with the self-constructed questionnaires. The reliability coefficient of Alpha Cronbach for the items in this study was 0.816. Pearson Correlation was used to test the relationships among motivational factors and academic performances in Chemistry among students. Results of the study showed that all seven factors studied were the factors in motivating students to learn Chemistry while friends was the most dominant factor among all. All seven factors were related to each other and the students’ academic performances in Chemistry. Implication of the study and recommendations for future research also being discussed.